Enhancing proficiency in performing endoscopic submucosal dissection (ESD) by using a prototype robotic endoscope - Chiu, Philip WaiYan; Phee, Soo Jay; Bhandari, Pradeep; Sumiyama, Kazuki; Ohya, Tomohiko; Wong, Jennie; Poon, Carmen CY; Tajiri, Hisao; Nakajima, Kiyokazu; Ho, Khek Yu (Endoscopy International Open, 2015)
Background and study aims: One of the challenges in performing endoscopic submucosal dissection (ESD) is the lack of counter traction during submucosal dissection. MASTER (Master and Slave Transluminal Endoscopic Robot) was designed to allow performance of complex endoluminal procedures using two arms with excellent control. This study aimed to compare the performance of ESD between endoscopists and novices using MASTER.Methods: This is a prospective study comparing the differences in performing ESD using MASTER in an ex vivo porcine stomach model among individuals with or without experience in surgery and endoscopy. Multiple standardized lesions of 20 mm2 were pre-marked on an ex vivo porcine stomach. Each participant received basic training in controlling MASTER before the ESD procedure. The operative time and size of specimen obtained by each participant were noted. Results: Nine individuals (three ESD expert endoscopists, three ESD non-expert endoscopists, and three non-clinician novices) participated in the experiment. All participants completed the ESD procedure for en bloc resection of standardized lesions using EndoMASTER without perforation. The mean times (mean ± SD) taken by ESD expert endoscopists, ESD non-expert endoscopists, and novices to complete Robotic ESD were 122 ± 58 s, 203 ± 150 s, and 561 ± 496 s, respectively. There was no statistically significant difference in the mean operative time to complete the ESD between the three groups (P = 0.242). When the performance of the six endoscopists was compared to that of the three novices, the endoscopists took an average of 162 ± 111 s to complete the ESD, while the non-clinicians required an average of 561 ± 496 s (P = 0.085). Conclusions: There was a trend to shorter operative time when comparing endoscopists to non-endoscopists in performing ESD using MASTER. The use of MASTER enabled the novice without endoscopy experience to complete the ESD procedure.